A structural equation model and effects of music on mental energy, mental toughness, psychological skills, mindfulness, athletic identity and sports performance among young basketball players in shandong province, China - Shaoshen, Wang (2025)
This study examines how psychological variables are related to sports performance and the effects of music interventions among young basketball players in Shandong Province, China, through a two-study research design. Study 1 (n=604) validated Chinese versions of six psychological measures and developed a structural equation model examining relationships between psychological variables and sports performance. Study 2 (n=42) explored the effects of different music interventions on these variables through a 12-week randomized controlled trial. Study 1's confirmatory factor analyses demonstrated excellent psychometric properties for all translated instruments: AMES-C, TMTIS-C, APSI-C, AIMSP-C, MAAS-C and SSS-C. All scales showed strong construct validity (CFI>0.94, RMSEA<0.06), convergent validity (AVE>0.50), discriminant validity, and test-retest reliability (ICC>0.89). The structural equation model revealed Mental Energy as a crucial mediator between psychological factors and sports performance, with Mindfulness (β=0.314, p<0.001), Psychological Skills (β=0.267, p<0.001), and Mental Toughness (β=0.238, p<0.001) showing significant direct effects on Mental Energy, which in turn influenced Sports Success (β=0.322, p<0.001). Study 2 demonstrated significant differential effects of music interventions on both psychological variables and basketball performance. Motivational music showed superior effects on complex motor tasks like dribble layup performance (MD=4.04, p<0.001), while self-selected music was more effective for precision tasks like shooting accuracy (MD=-6.86, p<0.001). Both music conditions significantly enhanced mental energy, psychological skills, and mental toughness compared to controls. This research provides empirical evidence supporting the integration of structured music sessions into athletic training programs, with findings suggesting that different types of music may be optimal for different aspects of basketball performance. The validated psychological measures and structural equation model offer valuable tools for future research and practical applications in sports psychology.